2013
DOI: 10.1245/s10434-013-2882-0
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Neoadjuvant Chemoradiation is Superior to a Surgery-First Approach in the Treatment of Pancreatic Head Adenocarcinoma

Abstract: Neoadjuvant chemoradiation for pancreatic cancer identifies patients with early metastases or poor performance status, who can be spared an ineffective or prohibitively morbid operation, and is associated with improved survival at significantly lower cost than a surgery-first approach. Neoadjuvant chemoradiation followed by surgery is a strategy that provides more cost-effective care than a surgery-first approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 32 publications
0
32
0
1
Order By: Relevance
“…The main potential advantages of neoadjuvant strategies are: i) increased resectability and likelihood of margin-negative resection, which is relevant, as patients with BRPAC or LAPAC exhibit a similar prognosis to those with immediately resectable PAC if R0 resection can be achieved (10); ii) increased likelihood of completion of multimodal treatment, which is possibly the most effective way to improve the outcome of patients with BRPAC or LAPAC; iii) prevention of unnecessary surgery in aggressive, treatment-resistant disease; iv) evaluation of chemo-sensitivity and increased patient's compliance (32); v) minimization of pancreatic leak without increase of postoperative complications (33-37); and vi) cost-effectiveness (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main potential advantages of neoadjuvant strategies are: i) increased resectability and likelihood of margin-negative resection, which is relevant, as patients with BRPAC or LAPAC exhibit a similar prognosis to those with immediately resectable PAC if R0 resection can be achieved (10); ii) increased likelihood of completion of multimodal treatment, which is possibly the most effective way to improve the outcome of patients with BRPAC or LAPAC; iii) prevention of unnecessary surgery in aggressive, treatment-resistant disease; iv) evaluation of chemo-sensitivity and increased patient's compliance (32); v) minimization of pancreatic leak without increase of postoperative complications (33-37); and vi) cost-effectiveness (38).…”
Section: Discussionmentioning
confidence: 99%
“…These studies are difficult to interpret, as they have used various definitions of BRPAC, different induction and post-resection regimens, and, if applied, incorporated varied radiation therapy plans (38)(39)(40)(41)(42). The most active regimens for advanced disease offer the best chance of achieving downstaging and systemic disease control.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NT is cost-effective and allows to “selectin” patients with localized disease whom would benefit most from resection, and avoid the morbidity of PD in patients who will demonstrate radiographic evidence of metastatic disease during the course of NT 3134 Currently, we lack the tools to accurately predict which patients are at risk for OAT and ER, and would therefore derive benefit from multimodality treatment upfront with NT; this is the strength of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the Surveillance, Epidemiology and End Results registry from 1994 to 2003 found that patients receiving neoadjuvant CRT have significantly higher rates of survival relative to non-neoadjuvant CRT (hazard ratio 0.55, 95% CI 0.38-0.79; p = 0.001) and adjuvant radiation therapy (hazard ratio 0.63, 95% CI 0.45-0.90; p = 0.03) [30]. Furthermore, neoadjuvant CRT is not only associated with improved survival, but also a significantly lower cost than surgery-first approaches [31]. …”
Section: Neoadjuvant Chemoradiationmentioning
confidence: 99%